1989
DOI: 10.1007/bf00332400
|View full text |Cite
|
Sign up to set email alerts
|

Duplications created by transformation in Sordaria macrospora are not inactivated during meiosis

Abstract: We present here the first report of a transformation system developed for the filamentous fungus Sordaria macrospora. Protoplasts from a ura-5 strain were transformed using the cloned Sordaria gene at a frequency of 2 x 10(-5) transformants per viable protoplast (10 per microgram of DNA). Transformation occurred by integration of the donor sequences in the chromosomes of the recipient strain. In 71 cases out of 74, integration occurred outside the ura5 locus; frequently several (two to four) copies were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The comparisons presented here indicate that the S. macrospora genome is eminently suitable for this purpose, because it is similar enough to be readily aligned at the nucleotide level even outside of coding regions, but has aquired a sufficient degree of dissimilarity especially in non-coding regions to provide an adequate signal-to-noise enrichment for distinguishing functional from non-functional sites. Another point of interest might be the fact that in S. macrospora, no indication of RIP (repeat-induced point mutation) has been found yet (Le Chevanton et al, 1989). RIP has originally been discovered in N. crassa where it inactivates duplicated sequences during the sexual phase of the life cycle (Selker et al, 1987).…”
Section: Which Additional Fungal Genomes Might Be Sequenced For a Commentioning
confidence: 98%
“…The comparisons presented here indicate that the S. macrospora genome is eminently suitable for this purpose, because it is similar enough to be readily aligned at the nucleotide level even outside of coding regions, but has aquired a sufficient degree of dissimilarity especially in non-coding regions to provide an adequate signal-to-noise enrichment for distinguishing functional from non-functional sites. Another point of interest might be the fact that in S. macrospora, no indication of RIP (repeat-induced point mutation) has been found yet (Le Chevanton et al, 1989). RIP has originally been discovered in N. crassa where it inactivates duplicated sequences during the sexual phase of the life cycle (Selker et al, 1987).…”
Section: Which Additional Fungal Genomes Might Be Sequenced For a Commentioning
confidence: 98%
“…(7,8) Finally, fungi provide unique examples of closely related organisms that in some cases show and in others do not show methylation: whereas methylation is found in representative species of the three major fungal taxa (the zygomycetes, the ascomycetes, and the basidiomycetes), it is undetectable in several ascomycete species. (9) These include Sordaria macrospora, (10) and Saccharomyces cerevisiae, (11) which are close relatives of the methylationcontaining species Neurospora crassa (3) and Candida albicans, (12) respectively. Levels of methylation vary greatly between organisms that display this modification.…”
Section: Distribution Of Dna Methylation Among Eukaryotesmentioning
confidence: 99%
“…Transformation studies of vector DNA in other fungi have demonstrated a wide range of frequencies of homologous integration. The rate is nearly 100% in Saccharomyces cerevisiae (22) and Candida albicans (17), 80% inAspergillus nidulans (34), and from 5 to 80% in Neurospora crassa depending on the host strain (5,7,15) but only 3% in Sordaria macrospora (21). Although the frequencies of these homologous recombina-* Corresponding author.…”
mentioning
confidence: 99%